BMS662: Microbial Pathogenicity / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2022)
This course is about how microbes cause disease. Emphasis is on medically important microorganisms. The relationship between pathogenicity and the lifestyles and structures of microbial pathogens will also be discussed. Selected model microorganisms are used to introduce the major concepts in microbial pathogenesis. Special emphasis will be on the mechanisms and strategies by which microbial pathogens attach, invade and multiply in a host; the host’s response and pathogens’ evasion strategies against the host immune system will also be discussed. Emphasis is also given to the molecular and genetic aspects of pathogenicity. The regulation of virulence factors and the evolution of bacterial pathogens will also be covered. Treatments for microbial infections will also be discussed.